A comparative study of analgesic effect between ultrasound-guided posterior vis-a-vis lateral transversus abdominis plane block in patients undergoing total abdominal hysterectomy with bilateral salpingo-oophorectomy under spinal anesthesia - Rajib Sikder; Sankar Roy; Arunava Biswas; Dipasri Bhattacharya (Asian Journal of Medical Sciences, 2025)
Background: Transversus abdominis plane (TAP) block is used to reduce pain after total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH+BSO). Two important approaches are ultrasound-guided lateral and posterior approaches. Ultrasound-guided blocks help in the correct localization of the plane and proper deposition of drugs. Aims and Objectives: This study was done to compare the analgesic effect of posterior TAP block and lateral TAP block in TAH+BSO. Materials and Methods: A double-arm observational study was conducted on eighty patients (ASA 1 and 2) posted for TAH+BSO under spinal anesthesia. They were randomly divided into two equal groups, 40 each (Groups L and P). Ultrasound-guided lateral TAP block and posterior TAP block were administered bilaterally with 20 mL 0.25% bupivacaine in the L group and P group, respectively, on each side of the abdomen after skin closure at the end of the operation. The intensity of post-operative pain was evaluated by a 10 cm Visual Analog Scale (VAS) Score at 1, 3, 6, 9, 12, and 24 h. If VAS was more than 4, 1 g paracetamol infusion was given. Duration of analgesia, total rescue analgesic requirement, and hemodynamic changes by measuring mean arterial pressure and pulse rate were also observed. Results: VAS score was significantly less in Group P than in Group L (P<0.05). The time of first rescue analgesia requirement was longer in Group P compared to Group L. Total analgesic requirement in 24 h was less in Group P compared to Group L. Hemodynamic changes were comparable in both groups. Conclusion: Posterior TAP block provides better post-operative analgesia than lateral TAP block with stable hemodynamics in patients undergoing TAH BSO operation under spinal anesthesia.